Influence of network connection and synchronisation for Hindmarsh–Rose model. (27th November 2012) - Jia, Qiuju; Chen, Zengqiang
In recent years, the chaotic synchronisation of neural networks has been an urgent problem. In this paper, a kind of small parameter r unmatched neuron network is considered. At first, the dynamical behaviours of the HR neuron model are analysed by the ISI diagram. A change of parameter r in small range will result in great change in the size of the chaos attractor and so, the significance of parameter r in the dynamic behaviour of neuron can be shown. Meanwhile, we also study the role of network connection types and coupling strength in the synchronisation of neuron network. It may play a significance role to neuroscience and clinical medicine research in the future.